Economic Analysis of Increasing Foot-and-Mouth Disease Vaccination Frequency: The Case of the Biannual Mass Vaccination Strategy - Ozturk, Nursen; Kocak, Omur; Vosough Ahmadi, Bouda (Frontiers in Veterinary Science, 2020)
Biannual mass vaccination is a routinely applied foot-and-mouth disease (FMD) control strategy in Turkey. However, because biannual mass vaccination may leave significant immunity gaps, this strategy may cause economic losses because of possible FMD infections. In high-risk areas—such as border cities, it was suggested by the government to increase the vaccination intervals in order to decrease the FMD infection risk. This study analyses and compares the economic effects of a biannual mass vaccination regime and vaccination every 4 months as an alternative strategy in border cities by using partial budgeting approach. Biannual mass vaccination was used as a baseline scenario. Data on the impact of FMD on animal health and production parameters for 2018 were obtained from the OIE-WAHIS system and complemented by literature data and expert opinion. In the partial budgeting model, weight loss was considered as a major loss of income because majority of the farming systems are based on cattle fattening in the border cities of Turkey. Results revealed that the net economic impact, which is the benefit that exceeds the losses and costs of increasing the frequency of vaccination, is 76.4 TL (15.9) per cattle. The sensitivity analysis showed that average body weight and weight losses when infected had more effect on net impact changes than market prices. The lower and upper FMD incidence variability resulted in 19.2 TL (4) and 190.8 TL (39.6) of net impact per cattle, respectively. The new FMD control strategy would make a total net economic impact of 5,274,836 TL (1,094,250) for a population of 800,970 fattening cattle in border cities. The results of this study indicated that intense FMD control strategies may be more cost effective than the current control strategies, especially in high-risk areas. Future studies with more comprehensive epidemiological and economic data must be conducted to analyze and compare alternative FMD control strategies in Turkey.